(untitled) (INNOVATIVE ECONOMY, 2025)
Samoilenko I.О. MECHANISMS FOR ENSURING ECONOMIC SECURITY AND STABILITY OF THE SOCIAL AND ECONOMIC SYSTEM IN THE CONTEXT OF CONTEMPORARY MILITARY-POLITICAL CHALLENGES Purpose. This article aims to identify the mechanisms level up economic security and stability of the social and economic system. By doing so, it seeks to develop and implement effective instruments for safeguarding the social and economic system against destructive factors of both internal and external origin. Methodology of research. The study employs a set of research methods, including induction and deduction (to formulate the theoretical foundations of economic security); analysis and synthesis (to identify the principal approaches to economic security and to reveal its categorical essence); a systems approach (to disclose the conceptual foundations and mechanisms of economic security); and formal and logical analysis (to determine the dominant factors in securing the economic security and stability of the social and economic system). Findings. The paper argues that economic security should be conceptualized as a state of reliable protection of the social and economic system against existing and potential threats from both internal and external environments. The study outlines and examines various approaches and mechanisms for ensuring the economic security of the social and economic system. Furthermore, it demonstrates the opportunities and advantages of applying Civil-Military Cooperation (CIMIC) under the conditions of contemporary military-political challenges. A model of the CIMIC system is presented. The paper posits that PMESII-PT analysis constitutes a practical and universal instrument that enables timely responses to changes in the civilian environment. Originality. The research contributes to the further theoretical conceptualization of economic security of the social and economic system in the context of military-political challenges. It advances existing scholarship by refining approaches to its interpretation, offering an original perspective on its conceptual essence, and substantiating the role of CIMIC in strengthening economic security. A model of the CIMIC system is presented. Practical value. The findings of this study hold practical significance, the use of civil-military cooperation as an effective institutional mechanism for increasing the level of economic security of the social and economic system is substantiated. The results may be of interest to scholars, policymakers, government authorities, and representatives of civil society organizations. Key words: economic security, social and economic system, approaches and mechanisms of provision, civil-military cooperation, PMESII-PT analysis.